Analisis Hubungan Tingkat Asupan Natrium dan Tingkat Stres dengan Tekanan Darah Karyawan Produksi PT Eurochair Internusa - Davena zulkurnia (PT Bukuloka Literasi Bangsa, 2026)
Hypertension is a major risk factor for cardiovascular disease and can be influenced by sodium intake and stress levels. This study aimed to analyze the relationship between sodium intake, stress levels, and blood pressure among production department employees at PT Eurochair Internusa. An analytical observational study with a cross-sectional design was conducted, involving 74 respondents selected through purposive sampling. Sodium intake was assessed using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), stress levels were measured using the DASS-21 questionnaire, and blood pressure was measured using a digital sphygmomanometer. Data were analyzed using Spearman’s rank correlation test. Results showed a significant association between sodium intake and systolic blood pressure (p=0.003; r=0.344), but not with diastolic blood pressure (p=0.379; r=0.104). Stress levels were not associated with systolic blood pressure (p=0.336; r=0.113), but showed a significant association with diastolic blood pressure (p<0.001; r=0.407). These findings indicate that limiting dietary sodium and managing occupational stress are critical preventive strategies for blood pressure control among industrial production workers. Keywords: blood pressure, employees, hypertension, sodium intake, stress